The diurnal and nocturnal floral scent of dracaena fragrans (L.) Ker Gawl. in Thailand - Jakaphun Julsrigival (2020)
© 2020 Chiang Mai University. Dracaena fragrans (L.) Ker Gawl., with its green leaves and attractive shape, is a popular ornamental plant in Thailand, used for both interior decorating and outdoor landscaping. Its fragrant flowers only bloom at night. This study investigated the volatile chemicals from the flowers of D. fragrans during the day and night. Volatile compounds were extracted by Head Space Solid Phase Micro-extraction (HS-SPME) technique and determined by Gas Chromatography-Mass Spectrometry (GC-MS). Thirty compounds were identified; sesquiterpenes were the most prevalent (α-farnesene, 23.1-50.8%). The composition of the volatile compounds from the flowers differed between day and night.